2010
DOI: 10.1002/qua.22854
|View full text |Cite
|
Sign up to set email alerts
|

On the shape dependence of cluster (hyper)polarizabilities. A combined ab initio and DFT study on large fullerene–like gallium arsenide semiconductor clusters

Abstract: The effect of the cluster shape on the magnitudes of the static dipole (hyper)polarizabilities of large gallium arsenic clusters built from 72 atoms is presented and discussed. Also, the performance of conventional and long range corrected density functionals is assessed on the prediction of the static electric dipole hyperpolarizabilities. The reported results obtained at the Hartree-Fock, (LC-) BLYP, (LC-) BPW91, (CAM)-B3LYP, and WB97XD levels of theory demonstrate that the cluster shape not only dominates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In recent years, there is an active and intense interest in our laboratory concerning the microscopic electrical response properties of a great assortment of semiconductor clusters1–11. The motivating scientific hypothesis that gears toward those investigations rely on the fascinating possibility of joining the prosper ground of nanomaterial design with the field of the nonlinear optics12.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there is an active and intense interest in our laboratory concerning the microscopic electrical response properties of a great assortment of semiconductor clusters1–11. The motivating scientific hypothesis that gears toward those investigations rely on the fascinating possibility of joining the prosper ground of nanomaterial design with the field of the nonlinear optics12.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the specific DFT limitation should hold for any molecular system regardless its nature. This is totally true; in two recent studies by Karamanis and Pouchan8 and Karamanis et al9, it has been shown that conventional DFT functionals lead to serious overestimations of the second hyperpolarizability even when inorganic nonconjugated systems are considered. In Ref 8,.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it would be interesting to compare the hyperpolarizabilities of Si 20 Li 20 with those of fullerene‐like gallium arsenic clusters that recently have been the subject of two electric property studies by Karamanis et al[41, 50] In the first of these studies, the hyperpolarizabilities of two large GaAs clusters built from 72 atoms and of different shapes have been reported, whereas in the second, the mean hyperpolarizability of a respective number of tubular GaAs clusters of increasing size have been analyzed. Our outcomes reveal that when the HF/cc‐pVDZ hyperpolarizability of Si 20 Li 20 (7.8×10 6 au) is compared with those obtained for both (GaAs) 36 clusters of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond boron nitride, there have been fewer studies of binary compounds comprised of other elements, and typically the focus has been on III-V and II-VI binary A n B n fullerenes with light elements [34][35][36][37][38][39][40][41][42][43][44][45][46] (A=boron, aluminum, zinc; B=nitrogen, phosphorus, oxygen, sulfur) and small size [34][35][38][39][40][41][42][43][44][45][46][47] (n=12). There are a few exceptions in the literature with heavier elements 45,[47][48][49] (A=gallium, cadmium; B=arsenic) and larger sizes [36][37][48][49] , and binary IV-IV Si 12 C 12 35 and homogeneous boron fullerenes [50][51] have also been considered. One notable exception is a study by Beheshtian and coworkers 34 who focused on a broader view of the role that element substitution plays in A 12 B 12 (A=boron, aluminum; B=nitrogen, phosphorus) fullerene properties.…”
Section: Introductionmentioning
confidence: 99%